PROSES SEMIOSIS PADA ALTAR GEREJA HKBP SURABAYA - Sitindjak, Ronald Hasudungan Irianto (Dimensi Interior, 2012)
Huria Kristen Batak Protestant is the largest Protestant church of the Lutherian denomination in the Batak society that was historically formed as a result of the RMG mission (Reinische Missions-Gesselschaft) from Germany. Apart from evangelising, their missions also brought in the building typologies of RMG churches in Germany to their Batak land, which can evidently be sensed from the HKBP church in Pearaja, Tarutung, Sumatera Utara. HKBP Pearaja has thus been a typological reference for many HKBP church builders throughout Indonesia, including HKBP Surabaya, in terms of their architectural and interior designs. This research is a qualitative study using the descriptive method of analysis and the approach of semiotics. The approach was adopted by Charles Sanders Peirce and this has been combined with theological intepretation to discover the relationships between the signs and symbols observed in the altar of HKBP Surabaya. This apprach emphasizes on the process of Semiosis that has taken place in the design of the church?s altar resulting in the formation of icons, index and symbols in the overall arrangement of the altar. Icons appear to be the most dominant form of signs and thus it can be concluded that the supportive elements of the altar that consist of the altar table, cross, cloth, candle and the ??(Alfa-Omega) symbol possess iconic relationships with the church altar of HKBP Surabaya. These signs themselves convey the theological messages of: ?God?s Ark?, ?Holy Communion?, ?Christianity?, ?Law of Love? and the ?Holy Trinity of Father, Son and Holy Spirit.?